Impact of early season jump loads on neuromuscular performance in division I Volleyball: Analyzing force, velocity, and power from countermovement jump tests - Sanders, G. J.; Skodinski, S.; Peacock, C. A. (Translational Sports Medicine, 2025)
The study investigated daily jump load variations on neuromuscular fatigue in nine NCAA Division I female volleyball athletes during the first 22 days of the season. Using force plates and inertial measurement units, data from 17 sessions were analyzed to assess relationships between jump loads and neuromuscular performance. Pearson`s correlations were calculated to assess the relationships between force, velocity, and power force plate metrics and jump variables (duration in minutes, total jump counts, and jump counts greater than 38.1 cm (Jumps 38+) and 50.8 cm (Jumps 50+)). Nine out of 14 force metrics showed weak-to-moderate negative correlations with Jumps 50+, indicating as the highest intensity of jump counts increased and force production decreased (r ranges from -0.194 to -0.570; p = 0.025 for all). In contrast, nine out of 16 velocity and power metrics showed weak-to-moderate positive correlations with Jumps 50+ (r ranges from 0.175 to 0.466; p = 0.044 for all). In total, 29 out of 36 force plate metrics were significantly correlated to Jumps 50+, the highest intensity jump threshold assessed. Monitoring high-intensity jump loads provides a more accurate and nuanced assessment of neuromuscular performance and fatigue than total jump counts or session duration, with implications for optimizing athlete readiness and performance.